THE BEHAVIOR OF FULFILLING THE BASIC NEEDS OF EARLY CHILDHOOD DURING COVID-19 PANDEMIC - Devi Arine Kusumawardani, S.Keb., M.Kes.; Elok Permatasari (UNIVERSITAS AIRLANGGA, 2023)
Background: In conditions of uncertainty and anxiety about pandemic conditions, children still have the right to have the opportunity to grow and develop optimally, both cognitively, mentally, and socially. Parents, as the primary caregivers of children at home and who hold the main responsibility for the growth and development of early childhood children, should meet the basic needs of children's growth and development. The basic needs of children's growth and development consist of 3 main aspects: Fostering, Asih, and Asah. Purpose: This study aims to analyze parenting behavior to fulfill early childhood growth and development needs during the Covid-19 pandemic. Methods: This research was conducted at Al Amien Jember Kindergarten from August to November 2020. The population in this study is all 282 parents of Al Amien Jember Kindergarten students. The sample size calculation uses the formula from Snedecor and Cochran with a sample size of 72 parents. Result: The results showed that most parents with good knowledge (80,56%) and good attitudes (80,56%) had good basic needs fulfillment behavior. The results of statistical analysis using the Spearman correlation test show a significant relationship between parental knowledge (p-value = 0.003) and parental attitudes (p-value = 0.000) with the behavior of fulfilling the basic needs of early childhood. Conclusion: Knowledge and attitudes of parents related to the parental behavior in meeting the basic needs of early childhood development. This study contributes to parenting during the COVID-19 pandemic so that children's growth and development remain optimal.